An update on the effectiveness of probiotics in the prevention and treatment of cancer - Vidya Sankarapandian; Balu Alagar Venmathi Maran; Ramya Lakshmi Rajendran; Manasi P. Jogalekar; Sridharan Gurunagarajan; Rajapandiyan Krishnamoorthy; Prakash Gangadaran; Byeong-Cheol Ahn (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Probiotics are living microbes that play a significant role in protecting the host in various ways. Gut microbiota is one of the key players in maintaining homeostasis. Cancer is considered one of the most significant causes of death worldwide. Although cancer treatment has received much attention in recent years, the number of people suffering from neoplastic syndrome continues to increase. Despite notable improvements in the field of cancer therapy, tackling cancer has been challenging due to the multiple properties of cancer cells and their ability to evade the immune system. Probiotics alter the immunological and cellular responses by enhancing the epithelial barrier and stimulating the production of anti-inflammatory, antioxidant, and anticarcinogenic compounds, thereby reducing cancer burden and growth. The present review focuses on the various mechanisms underlying the role of probiotics in the prevention and treatment of cancer.